أهمية استخدام أجهزة الانارة LED في إدارة الطلب على الطاقة في معمل اسمنت طرطوس - ديوب, علاء (Latakia University Journal -Engineering Sciences Series, 2019)
The lighting provided a key and important role that can be played in rationalizing the demand for electricity in the industrial sector by reducing the consumption of electrical energy needed for lighting using energy-saving lighting devices on the one hand and improving the management and control of lighting on the other hand, in addition to reducing the load of air conditioning resulting from excessive lighting .This can be done by increasing knowledge and awareness about energy-saving lighting techniques and systems, good management and optimal use, and the use of standard standards adopted in this area. In this study, work has been done to draw attention to the importance of the use of LED devices in the field of lighting at the Tartous Cement Factory to be a practical scientific study on the economic feasibility of LED lighting devices in the industrial field with high energy consumption in the field of lighting. يمكن ترشيد الطلب على الطاقة الكهربائية في القطاع الصناعي وذلك من خلال تخفيض استهلاك الطاقة الكهربائية اللازمة للإنارة باستخدام أجهزة إنارة موفرة للطاقة من ناحية وتحسين الادارة والتحكم بالإنارة من ناحية أخرى، إضافة الى تخفيض حمل التكييف الناتج من الانارة الزائدة. ويمكن أن يتم ذلك من خلال زيادة المعرفة والوعي حول تقنيات ونظم الانارة الموفرة للطاقة والإدارة الجيدة والاستخدام الامثل لها واستخدام المواصفات المعيارية المعتمدة في هذا المجال. في هذه الدراسة تم العمل على تأكيد أهمية استخدام أجهزة الليد LED (Light Emitting Diodes) في مجال الانارة في مصنع اسمنت طرطوس لتكون دراسة علمية عملية حول الجدوى الاقتصادية لأجهزة الانارة LED في المجال الصناعي ذي الاستهلاك الكبير للطاقة في مجال الانارة.